Montesquieu’s anti-utopian political theory - Gerrans, Philip (2008)
Montesquieu’s anti-utopian political theory (2008) 1er septembre 2013, par Gerrans, Philip John West-Sooby (dir.), Nowhere is perfect. French and francophone utopias/dystopias, Newark, University of Delaware Press, 2008, p. 11-26.
Keywords: exportSPIP